Cholangioscopy-guided holmium laser lithotripsy of a stone trapped in a mechanical lithotripter - Libânio, Diogo (2018)
Large common bile duct (CBD) stones can be removed with mechanical lithotripsy, although over-the-basket techniques such as electrohydraulic or pulsed dye laser lithotripsy can be necessary in cases of stone impaction.1 We report the case of a 42-year-old woman with a 30-mm stone in the CBD in whom mechanical lithotripsy was attempted after wide sphincterotomy. However, during the procedure, a rupture occurred in the traction wire of the basket, next to the handle. Emergency lithotripsy (EL) with use of an external-type system was immediately attempted, but wire fracture occurred again (2 times), turning its length shorter than the metallic sheath of the EL and rendering EL impossible